Wildlife status and ecotourism potentials of Lekki Conservation Centre, Lagos, Nigeria - Ojonugwa Ekpah (Goodwood Publishing, 2021)
Purpose: Information about the status of wildlife in Lekki Conservation Centre (LCC) which is required for biodiversity policy-making is lacking. Methods: Day foot patrol to monitor wildlife in LCC was carried out and the wildlife species present were identified from January to December 2020. Data of animals sighted in the patrol and by the tourists were compared with records of animals sighted from March to July 2010 as recorded in the Protection Report Diary. Results: The findings indicated a decline in the population of squirrel (Heliosciurus gambianus) and bushbuck (Tragelaphus scriptus). Limitation: A list of fauna in LCC forest is provided as a result of the foot patrol although, some parts of the forest were inaccessible. Contribution: The perception of ecotourists is highlighted which can serve as feedback about their experience with the resources useful for biodiversity policy. Conclusion: Species diversity in the Protection Report Diary (in 2010) was higher compared to the total number of wildlife species sighted by visitors (in 2021) and during the patrol (in 2020) indicating that some wildlife species in LCC declined within 10years.